The art of political warfare - Pitney, John J. (Norman, OK University of Oklahoma Press, 2000)
The Art of Political Warfare highlights the striking similarities between politics and war. Applying military thought to domestic politics, John J. Pitney, Jr., persuasively argues that the language of war teaches us about political activity. Combining lively story telling with solid scholarship, he ranges across history to produce a unique field manual for politics.
ncludes bibliographical references (p. 201-237) and index.
Keywords: Politics, Practical